Considerations for sports federations/sports event organizers when planning mass gatherings in the context of COVID-19 Interim guidance (World Health Organization, 2020)
This sports addendum should be read in conjunction with the WHO key planning recommendations for Mass Gatherings in the context of the current COVID-19 outbreak which provides general advice on the public health aspects of such events. This addendum has been developed to provide additional support to sports event organizers in assessing the specific additional risks, identifying mitigation activities and making an informed evidence-based decision on continuing to host any sporting event. Additional guidance is provided in the specific WHO COVID-19 mass gatherings sports addendum risk assessment tool and mitigation checklist. Updated technical guidance on COVID-19 should also be consulted. These documents will be reviewed and updated as the pandemic evolves.